- #1

rishi kesh

- 35

- 3

## Homework Statement

This is a silly question,but i have a problem.How do we solve derivative of -x using first principle of derivative. I know that if derivative of x w.r.t x is 1 then ofcourse that of -x should be -1. Also it can be solved by product rule taking derivative of -1.x .

## Homework Equations

## The Attempt at a Solution

Here is how i attempted it:

f(x)= -x

f(x+h)= -x+h

Using first principle :

dy/dx = [-x+h-(-x)]/h

= h/h

= 1

what is wrong here?please help. Thanks in advance